2000
DOI: 10.1111/j.1365-2141.2000.02502.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of venous thromboembolism in family members with mutations in the genes of factor V or prothrombin or both

Abstract: Summary. Factor V Leiden and the G20210A mutation in the prothrombin gene are the most frequent abnormalities associated with venous thromboembolism. It is unknown whether the risks due to the presence of either mutation are of the same magnitude. We compared the prevalence and incidence rate of venous thromboembolism in relatives with either mutation or both. The finding of different rates might influence the strategies for primary prevention of thrombosis in carriers of these mutations. The study population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 31 publications
1
49
1
2
Order By: Relevance
“…Heterozygous carriers constitute approximately 2% of the general Caucasian population, and reach 20% in the population with recurrent or familial thrombotic events (47,48). Heterozygous subjects for the G20210A mutation carry an estimated two-to five-fold increased risk of venous thrombosis without other concomitant risk factors, and a more than additive synergistic risk of VTE when other thrombophilic risk factors, particularly factor V Leiden, are simultaneously present (47)(48)(49). The risk of VTE is remarkably increased in women heterozygous for prothrombin G20210A polymorphism who are taking OC (37)(38)(39)(50)(51)(52).…”
Section: Prothrombin G20210amentioning
confidence: 99%
“…Heterozygous carriers constitute approximately 2% of the general Caucasian population, and reach 20% in the population with recurrent or familial thrombotic events (47,48). Heterozygous subjects for the G20210A mutation carry an estimated two-to five-fold increased risk of venous thrombosis without other concomitant risk factors, and a more than additive synergistic risk of VTE when other thrombophilic risk factors, particularly factor V Leiden, are simultaneously present (47)(48)(49). The risk of VTE is remarkably increased in women heterozygous for prothrombin G20210A polymorphism who are taking OC (37)(38)(39)(50)(51)(52).…”
Section: Prothrombin G20210amentioning
confidence: 99%
“…Although several case‐control and family studies suggest that prothrombin gene mutation G20210A (PT G20210A) is associated with an increased risk of venous thrombosis [1–5], the clinical relevance of the identification of heterozygous carriers of this mutation in daily practice is still under discussion. The benefits coming from an early identification of a carriership status among asymptomatic subjects in terms of appropriate prophylaxis measures should be balanced against the costs involved and the inconvenience of labeling otherwise healthy people as having ‘a disease’.…”
Section: Demographic and Clinical Characteristics Of Family Members Wmentioning
confidence: 99%
“…Because of the high prevalence of these two genetic polymorphisms, the gene‐to‐gene and gene‐to‐environment interaction is likely to play a major role in the development of thromboembolic complications. Several case–control and family studies have indeed shown a higher thrombotic risk in carriers of both defects than in carriers of a single polymorphism [1–6].…”
Section: Introductionmentioning
confidence: 99%